Model Spreadsheet Excel Aplication sebagai Pengolahan Hasil Belajar Peserta Didik dalam Penilaian Kurikulum 2013 - Khusnuddin, Khusnuddin (Jurnal Kependidikan, 2018)
This paper aims to describe the model of learning outcomes of learners in the assessment of the 2013 curriculum using excel aplication spreadsheet. Utilization of spreadsheet of excel aplication in processing learners’ learning results in Curriculum 2013 is based on several considerations, among others are the changes of assessment pattern from just displaying value in the form of numbers into numeric value accompanied by descriptive achievement of student competence, which require high accuracy for teacher to record descriptive achievement learning outcomes of learners; implementation of thematic learning accompanied by reports of learning outcomes using a subject approach requires an analytical step in mapping into subject content; speed and accuracy in data processing can lead to progress in the service of report cards; and the development of technology and computer information allows to help simplify the process of assessing the learners’ learning outcomes.